Higgs Bosons Near 125 GeV in the NMSSM with Constraints at the GUT Scale - Ulrich Ellwanger; Cyril Hugonie (Advances in High Energy Physics, 2012)
We study the NMSSM with universal Susy breaking terms (besides the Higgs sector) at the GUT scale. Within this constrained parameter space, it is not difficult to find a Higgs boson with a mass of about 125 GeV and an enhanced cross-section in the diphoton channel. An additional lighter Higgs boson with reduced couplings and a mass ≲ 123 GeV is potentially observable at the LHC. The NMSSM-specific Yukawa couplings λ and κ are relatively large and tan β is small, such that λ, κ, and the top Yukawa coupling are of 𝒪(1) at the GUT scale. The lightest stop can be as light as 105 GeV, and the fine-tuning is modest. WMAP constraints can be satisfied by a dominantly Higgsino-like LSP with substantial bino, wino, and singlino admixtures and a mass of ~60–90 GeV, which would potentially be detectable by XENON100.